An environmental impact comparison of disposable wood pallets and reusable steel cradles: A case study on rolled steel coils in container shipping in South Korea. Issue 5 (3rd May 2020) - Choi, Bulim; Yoo, Seungwoo; Lee, Kang-Dae; Park, Su-il
Abstract: When exporting rolled steel coils in shipping containers, it is required to fasten the cargo safely in a freight container using a special pallet for lashing and shoring such as wood dunnage or a coil cradle. This study aims to evaluate the environmental impact of coil cradles as a function of number of reuses, compared to disposable wood dunnage, through a case study based on container shipping of rolled steel coils in South Korea. The life cycle assessment method was applied for the comparison of the products. Under this analysis conditions, reusable coil cradle had lower environmental impact after 20 uses compared with disposable wood dunnage. Furthermore, the reusable coil cradle should be designed for at least 25 uses for lower impact in every environmental impact category compared with traditional wood dunnage. This study concludes that the environmental impact comparison between disposable wood dunnage and reusable coil cradles could provide useful information to policy makers and producers who determine the frequency of coil cradle reuse in rolled steel coil container shipping.